Effects of Combined Use of Trospium Chloride and Melatonin on In Vitro Contractility of Rat Urinary Bladder - Onur, Rahmi; Ozcan, Mete; Tuygun, Ugur; Ozan, Tunc; Ayar, Ahmet; Orhan, Irfan (Elsevier Science Inc, 2010)
OBJECTIVES To examine the effects of combined use of trospium chloride and melatonin on in vitro contractility of rat urinary bladder. METHODS Isolated bladder strips from 20 male Wistar rats were examined in an organ bath. Contractions were evoked by acetylcholine (ACh). Initially, effective concentrations of trospium and melatonin to inhibit the contractions were determined. We subsequently tested the effects of combined use of melatonin and trospium on agonist-induced contractions. RESULTS Exposure of bladder strips to 10 mu M ACh significantly increased the contractions. After cumulative administration of increasing concentrations of trospium (1, 3, and 5 mu M), agonistinduced contractions decreased significantly (P <.05). Similarly, the mean peak amplitude of contractions evoked by ACh was significantly inhibited by melatonin in a concentration-dependent manner (100, 200, and 300 mu M) (P <.05). Further evaluation of the effects of combined use of trospium and melatonin on ACh-induced contractions of bladder strips revealed that one-tenth of initially applied dose of trospium (500 nM) in addition to the lowest inhibitory dose of melatonin (100 mu M) significantly lowered both the peak amplitude and area under the contractility curve of contractions (P <.05). CONCLUSIONS Our results showed that combined use of low dose trospium and melatonin had strong in vitro inhibitory capability on agonist-induced contractions of rat bladder strips. The present findings may offer an insight into lowering the dose of an antimuscarinic by combining it with an antioxidant and endogenous hormone, melatonin. UROLOGY 75: 873-878, 2010. (C) 2010 Elsevier Inc.
Keywords: Overactive Bladder; Detrusor Instability; Incontinence; Antagonists; Invitro; Tract